Diseases in coral aquaculture: causes, implications and preventions - Sheridan, Christopher (2018)
Aquacultured corals are typically reared in dense in situ (mariculture) or ex situ (in aquaria) culture facilities. This high density rearing method makes these corals particularly vulnerable to specific diseases since virulence and communicability of pathogens have been shown to increase with host density. As such, entire production lines may be threatened. Maricultured corals are particularly at risk as the diversity of both diseases and of affected coral species in the marine environment is on the rise. Coral diseases are now a major driver of coral mortality on all reef systems from the Indo-Pacific through to the Caribbean and not only affect species in situ, but can be inadvertently transported into the culture systems. The avoidance of disease outbreaks in culture systems is of upmost importance and the mitigation of diseases in these systems is vital in the maintenance of healthy cultures. Although the study of naturally occurring coral diseases has become a popular and relatively well-studied topic over the last few decades, the effects of these diseases on coral husbandry and aquaculture are still virtually unknown. Aquaculture of corals is a developing industry, both for stocking the ornamental industry and for restoration purposes. This overview outlines what is known about coral diseases in aquaculture; what implications these diseases have on this activity; what may be the causes of the disease outbreaks in these systems, as well as what methods are available for maintenance of healthy stocks and for mitigation once a disease has been observed.